VOICES OF INCULTURATION IN AFRICA : IN THE PAST, IN THE PRESENT AND THE FUTURE - Ugwuanyi, Chikere (Asian Horizons, 2011)
When one speaks of inculturation, the mind would ordinarily race to the “mission territories” where people want to be rooted in their cultures but desire to be Christians as well. At one level, this is wrong because the Christian life itself is inculturation: Christian faith requires continuous movement to a better relationship with Christ. At another level, inculturation is needed more in those places where Christianity is still young; where the language, symbols and gestures of Christianity are unfamiliar to its adherents. Africa is one such place. It is the desire to remain fully African and fully Christian that makes inculturation a privileged discussion in African Christian life. When one looks carefully at the joy and hopes, pains and anxieties of life of faith in Africa, one would see a domineering concern about inculturation. Inculturation gets attention because many pastors are ever desirous to explain the gospel in a manner that makes sense to the mind and heart of people in Africa. The anxiety comes, not on whether there is a need for inculturation, but on how to proceed about it. This paper sets out to examine the experiences of the African Christians in their efforts to remain authentically African and truly Christian through inculturation efforts. I call those efforts ‘voices’ because at one time, one hears dissent, at another affirmation; at one moment, off notes, at another harmony. To capture the high, low and level waves that those voices produce, I have opted for a historical narrative of the efforts of inculturation in Africa. What is encouraging is that when one interprets the Christian life in Africa through its inculturation efforts, one has a high hope that the desires of the pastors are genuine and are actually addressed. The hope is based on outstanding results already on the ground, the current enthusiasm and vitality with which Africans discuss inculturation and a clear vision for the future. One can only wait, pray and work for a deeper incarnation of Jesus in African soil, attitude and mentality.